Influence of Yttria Nanoparticles on the Distribution of Interstitial Atoms in Sintered Iron - M.I. Cherednyk; O.Yu. Popov; O.Yu. Kumurgi; A.V. Rutkovskiy (Журнал нано- та електронної фізики)
The influence of Y2O3 nanoparticles on structure and interstitial atoms distribution in sintered iron is investigated. Scanning electron microscopy and energy-dispersive analysis showed that yttrium oxide particles provoked globular ferrite structure formation. Investigation of nitrogen atoms distribution on the material surface did not prove the theory about interstitial defects accumulation near yttria inclusion surface.